Critical Discourse Analysis Pairing Jokowi-Prabowo in Online Media Tribunnews.com - Rachmat Hidayat (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to describe through the dimensions of critical discourse analysis (AWK) the Teun Van Dijk model on the discourse of a duet of President Joko Widodo (Jokowi) and Prabowo through the online media channel Tribunnews.com for the period of June 2021. All data in this study were analyzed using technical methods qualitative. Tribunnews.com journalists who were researched in their reports tended to be critical, accompanying the discourse on the Jokowi-Prabowo duet that was previously presented to the public. Criticizing the discourse that is fed with various points of view, as well as wanting to show identity or ideology as a message-feeding medium, without any intervention from any party, including the authorities.